2019
DOI: 10.1002/ehf2.12447
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbilirubinaemia after cardiac surgery: the point of no return

Abstract: Aims The occurrence of hyperbilirubinaemia after heart surgery using cardiopulmonary bypass or post‐operative heart failure is fairly common. We investigated the incidence, predictive value, and post‐operative outcome of hyperbilirubinaemia after cardiac surgery in an effort to identify potential risk factors and significance on clinical outcome. Methods and results Between 2006 and 2016, 1272 (10.1%) out of 12 556 patients developed hyperbilirubinaemia, defined as bilirubin concentration >3 mg/dL, during post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 14 publications
0
50
3
Order By: Relevance
“…Aging indicated diminished functional capacity of the liver and added to the cumulative burden in the case of developed hyperbilirubinemia. Additionally, different from the a recent study outlining the increased risk of mortality for patients with hyperbilirubinemia after cardiac surgery associated with time to peak bilirubin, [29] our study indicated that peak TB concentration was an independent driver of in-hospital mortality for patients with severe hyperbilirubinemia after AAD surgery. And, we found out that the optimal cut-off value of peak TB on predicting in-hospital mortality was 121.2 µmol/l.…”
Section: Risk Factors Of In-hospital and Long-term Mortalitycontrasting
confidence: 99%
See 3 more Smart Citations
“…Aging indicated diminished functional capacity of the liver and added to the cumulative burden in the case of developed hyperbilirubinemia. Additionally, different from the a recent study outlining the increased risk of mortality for patients with hyperbilirubinemia after cardiac surgery associated with time to peak bilirubin, [29] our study indicated that peak TB concentration was an independent driver of in-hospital mortality for patients with severe hyperbilirubinemia after AAD surgery. And, we found out that the optimal cut-off value of peak TB on predicting in-hospital mortality was 121.2 µmol/l.…”
Section: Risk Factors Of In-hospital and Long-term Mortalitycontrasting
confidence: 99%
“…In previous studies, older age had been identified as an independent risk factor of mortality for patients with hyperbilirubinemia after cardiac surgery. [29] In our present study, older age was established a risk factor for in-hospital mortality for patients with hyperbilirubinemia after AAD surgery as well. Aging indicated diminished functional capacity of the liver and added to the cumulative burden in the case of developed hyperbilirubinemia.…”
Section: Risk Factors Of In-hospital and Long-term Mortalitymentioning
confidence: 59%
See 2 more Smart Citations
“…[6,7,[11][12][13] For patients undergoing cardiac surgery with cardiopulmonary bypass (CPB), recent study suggested that severe hyperbilirubinemia (5 times the normal upper limit) instead of mild bilirubin signi cantly increased patient mortality and a maximum bilirubin of 25.5 mg/dl was associated with 99% mortality. [14] Mild or moderate hyperbilirubinemia might be associated with hemolysis, cardiotomy suction, gaseous micro-emboli, and blood transfusions during CPB, which were temporary and revisable. However, severe hyperbilirubinemia could induce oxidative stress and cell apoptosis, which cause respiratory failure, thrombocytopenia, and even neurological dysfunction, and consequently promote multiple organ dysfunction syndrome (MODS) and increase patient in-hospital mortality.…”
Section: Introductionmentioning
confidence: 99%